Relatively Benign Sickle-cell Anaemia in 60 Patients Aged Over 30 in the West Indies. Issue 5610 (13th July 1968) - Serjeant, G. R.; Richards, R.; Barbor, P. R. H.; Milner, P. F.
Abstract : A study in Jamaica of 60 patients with sickle-cell anaemia over the age of 30 years showed that most of them were in full-time employment. Pains in the bones or joints, leg ulceration, and jaundice were the most frequent types of presentation, but only two patients had a haemoglobin level consistently below 6 g./ 100 ml. Most of the patients were well developed and of average height, and, though the development of secondary sexual characteristics was delayed, there was an average of 2.6 pregnancies per patient. These findings suggest that the course is more benign than has been realized.